The dark-thirty : Southern tales of the supernatural - McKissack, Pat, 1944-2017.; Pinkney, J. Brian (New York : Scholastic Inc., 1992)
A collection of ghost stories with African American themes, designed to be told during the Dark Thirty--the half hour before sunset--when ghosts seem all too believable.
Reprint: Originally published: New York : Knopf, c1992.
"First Scholastic printing, October 1993"--Verso t.p.
Keywords: Ghost stories, American; Horror tales, American; African Americans -- Juvenile fiction; Children's stories, American; Ghosts -- Fiction; Horror tales; African Americans -- Fiction; Short stories